Tritium breeding calculation in a stellarator blanket - Chernitskiy, S.V.; Moiseenko, V.E. (Вопросы атомной науки и техники, 2019)
In current blanket projects, tritium breeding ratio (TBR), the ratio of tritium production rate to the neutron production rate, is low (1.1…1.2). The MCNPX Monte-Carlo code has been used to model the neutron kinetics and to look for a principal possibility of increase TBR within a stellarator blanket limited space.